Safety surveillance for PrEP in pregnant and breastfeeding women - Fairlie, Lee; Lavies, Diane; Kalk, Emma; Mhlongo, Otty; Patel, Faeezah; Technau, Karl-Günter; Mahtab, Sana; Moodley, Dhayendre; Subedar, Hasina; Mullick, Saiqa; Sawry, Shobna; Mehta, Ushma (Frontiers in Reproductive Health, 2023)
The risk of HIV acquisition is higher during pregnancy and postpartum than other times. Newly acquired maternal HIV infection associated with high primary viraemia, substantially increases the risk of vertical HIV transmission. Pre-exposure prophylaxis (PrEP) reduces the risk of HIV acquisition.Currently available products include oral tenofovir/emtricitabine (TDF/FTC) and tenofovir alafenamide (TAF)/FTC), long-acting cabotegravir (CAB-LA) and the dapivirine ring (DVR). All except oral TDF/FTC have limited safety data available for use in pregnant and breastfeeding women. The safety of new PrEP agents for pregnant women and the fetus, infant and child, either exposed in utero or during breastfeeding is an ongoing concern for health care workers and pregnant and breastfeeding women, particularly as the safety risk appetite for antiretroviral (ARV) agents used as PrEP is lower in pregnant and breastfeeding women who are HIV-uninfected, compared to women living with HIV taking ARVs as treatment. With the widespread rollout of TDF/FTC among pregnant women in South Africa and other low-middle income countries (LMIC) and the potential introduction of new PrEP agents for pregnant women, there is a need for safety surveillance systems to identify potential signals of risk to either the mother or fetus, measure the burden of such a risk, and where appropriate, provide specific reassurance to PrEP users. Safety data needs to be collected across the continuum of the product life cycle from pre-licensure into the post-marketing period, building a safety profile through both passive and active surveillance systems, recognising the strengths and limitations of each, and the potential for bias and confounding.Pharmacovigilance systems that aim to assess the risk of adverse birth outcomes in pregnant women exposed to PrEP and other agents need to consider the special requirements of pregnancy epidemiology to ensure that the data derived from surveillance are sufficiently robust to inform treatment policies. Here we review the known safety profiles of currently available PrEP candidates in women of child-bearing potential, pregnancy and breastfeeding and discuss pragmatic approaches for such surveillance in HIV-endemic LMICs. (329 words).